Removal of Crystal Violet Dye by Electrocoagulation – Analysis of Electrode and Solution Changes - Senka Gudić; Ladislav Vrsalović; Nediljka Vukojević Medvidović; Sandra Svilović; Silvia Ivančić (Kemija u Industriji, 2024)
This study investigates the changes at the electrodes and in the solution during crystal violet dye removal by electrocoagulation at different current densities (0.016, 0.024, and 0.032 A cm−2) and initial pH values (3.2, 5.5, and 7.0). The electrocoagulation process, which lasted 50 min, revealed changes in pH, temperature, electrical conductivity, and concentration of the crystal violet dye in the solution. The results demonstrate complete removal of crystal violet dye at the highest current density (achieved after 40 min) and an initial pH of 5.5 (complete removal after 30 min). During the electrocoagulation process, both the anodic and cathodic electrode materials were consumed. The consumption of electrode material increased with higher current density and solution pH, the influence of current density being more pronounced. Examination of the electrode surfaces under a light microscope revealed that the anodes dissolved uniformly and locally during the electrocoagulation process, while the cathodes mostly underwent uniform corrosion.